(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: A descriptive study described clinical, paraclinical characteristics in children with the Alpha Variant of COVID-19 in Hai Duong Province. Study subjects and methods: We collected 53 children with the Alpha Variant of COVID-19 in Haiduong Province who were admitted from January to March. Results: Results showed that boys were 54.7%, and the average age was 7.5 ± 4.5 years. The most symptom was cough (16%), diarrhea (9.4%), and 77.9% of children with the Alpha Variant of COVID-19 without symptoms. Investigation showed that in 16.9% of patients with thrombocythemia, 15.1% of patients with leukocytosis, 16.9% of patients increase D-dimer in serum, and 13.2% of patients with the increased liver enzyme. In addition, 11.3% of patients had plunge lessons on chest X-rays. Conclusion: Clinical, paraclinical characteristics in children with the Alpha Variant of COVID-19 were not severe.